PENERAPAN PEMBELAJARAN DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA SISWA - Yosephina yanita Sargaling; Maria Trisna Sero Wondo; Stefania Baptis Seto (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aims to determine (1) student activities in the learning process after applying a scientific approach to class VII of SMPK Maria Goretti Ende for the 2021/2022 academic year; (2) improving students' mathematical literacy skills through a scientific approach to class VII SMPK Maria Goretti Ende for the 2021/2022 academic year. The type of research used is classroom action research (PTK). PTK is carried out in two cycles where each cycle is carried out in two meetings through four stages: planning, implementation, observation, and reflection. The data collection technique is a test of mathematical literacy ability and observation of the implementation of learning. Data analysis uses qualitative that describes student activities during the learning process and calculates the percentage of student learning completion with a completion level of 75%. The results showed that the application of learning with a scientific approach can increase student activity and mathematical literacy skills. This can be seen from the results of observations of student activities during the learning process in the first cycle reached 66% while in cycle II it increased by 90%. This means that there is an increase of 24%; and the percentage of completion of students' mathematical literacy ability in cycle I reached 65% with an average of 72 while in cycle II it reached 90% with an average of 85. It is proven that the application of learning with a scientific approach can increase student activity and students' mathematical literacy skills.